1987
DOI: 10.1007/bf00283629
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 22 in a newborn with multiple malformations

Abstract: A case of complete trisomy 22 in a live-born female child with multiple malformations is reported. The karyotype of the index patient had 46 chromosomes, with one chromosome 22 missing and one supranumerary metacentric chromosome. Different banding methods and in situ hybridization revealed that the extra chromosome consists of the long arms and a part of the short arms of two chromosomes 22. Our report supplies further proof that a fetus with complete trisomy 22 can occasionally survive to term, but the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Hirschhorn et al [1973] reported the first Gbanded proven case. All reported cases have had 47 chromosomes due to an additional chromosome 22, except for one report with a possible t(21;22) [Lalchev et al, 1978] and one with a 46,XX,+idic(22)(qter→p1125:: p1125→qter) karyotype [Voiculescu et al, 1987]. We describe a further case of trisomy 22 with a modal chromosome number of 46 but with a monocentric, possible isochromosome.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Hirschhorn et al [1973] reported the first Gbanded proven case. All reported cases have had 47 chromosomes due to an additional chromosome 22, except for one report with a possible t(21;22) [Lalchev et al, 1978] and one with a 46,XX,+idic(22)(qter→p1125:: p1125→qter) karyotype [Voiculescu et al, 1987]. We describe a further case of trisomy 22 with a modal chromosome number of 46 but with a monocentric, possible isochromosome.…”
Section: Introductionmentioning
confidence: 78%
“…Robinson and Kalousek [1996] strongly support that placental mosaicism would be necessary for a complete trisomy 22 fetus to reach term gestation. Survival of live-born individuals with complete trisomy 22 is short, usually a few hours to days [Voiculescu et al, 1987;Crowe et al, 1997;Feret et al, 1991]. The longest sur- vival (almost 3 years) was reported by Kukolich et al in 1989.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our family declined investigations aiming at determination of the parental origin of the additional chromosome 22. In addition to free trisomy 22, the literature provides examples of putative isochromosomes and translocations involving chromosome 22 [Voiculescu et al, 1987;Manasse et al, 2000]. Presence of an isochromosome 22 has been described for a trisomy 22 mosaic child [Guze et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal physical manifestations associated with trisomy 22 include intrauterine growth retardation, apparently low-set malformed ears, flat nasal bridge, bilateral epicanthal folds, hypertelorism, cleft lip and palate, micrognathia, prominent occiput, downward slant of palpebral fissures, short webbed neck, abnormal hands and feet, congenital heart defects, renal malformations, genital anomalies, and other malformations [Iselius et al, 1978;Vohra et al, 1987;Voiculescu et al, 1987, Isada et al, 1990Kukolich et al, 1989;McPherson et al, 1990;Sundareshan et al, 19901. Hypoplasia of the lungs and diaphragm have been reported [Iselius et al, 1978;Voiculescu et al, 19871, but diaphragmatic hernia has not been reported to be associated with trisomy 22.…”
Section: Introduction Trisomy 22 Is Rare In Liveborn Infantsmentioning
confidence: 97%